Cavernicolous Arrhopalites abchasicus sp. nov. (Collembola: Symphypleona: Arrhopalitidae) from the West Caucasus with a key to the World species of the genus - Vargovitsh, Robert S. (Zootaxa, 2013)
A new troglobiont species of Collembola, Arrhopalites abchasicus sp. nov., from Psyrtskha Cave in Novy Afon (West Caucasus, Abkhazia) is described. Subdivision of the genus Arrhopalites on diversus, caecus and harveyi groups of spe-cies is proposed and identification key to the World species is provided.